2020
DOI: 10.1063/5.0020941
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological law for the acoustic reflection by an array of cylindrical cavities in a soft elastic medium

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Up till now, only a few finite element methods (FEMs) have been performed to study the effect of various hydrostatic pressures like commercial FEM software ANSYS and COMSOL. 24,28,29 Through ANSYS simulating insulation coating with cylindrical cavities, it is found that the average thickness of the layer gets reduced, and the average diameter of the hole also gets smaller. 30 More systematic studies about the numerical modeling for underwater sound absorption at various hydrostatic pressures are required.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, only a few finite element methods (FEMs) have been performed to study the effect of various hydrostatic pressures like commercial FEM software ANSYS and COMSOL. 24,28,29 Through ANSYS simulating insulation coating with cylindrical cavities, it is found that the average thickness of the layer gets reduced, and the average diameter of the hole also gets smaller. 30 More systematic studies about the numerical modeling for underwater sound absorption at various hydrostatic pressures are required.…”
Section: Introductionmentioning
confidence: 99%
“…For airborne sound, the constraints of the causality principle dictate that the thickness of the sample must satisfy the following relationship [22] : 1 where is the bulk modulus of air, is the effective bulk modulus of the sample and represents the absorption spectrum with respect to the wavelength . Numerous researchers have attempted to achieve subwavelength acoustic structure design within the con nes of the minimum thickness limit [23][24][25][26][27][28][29][30][31][32][33][34] . Recently, Mak et al [35] used a soft boundary to circumvent the minimum thickness…”
Section: Introductionmentioning
confidence: 99%